PENGARUH MEDIA AUGMENTED REALITY TERHADAP PEMAHAMAN SISWA PADA KONSEP SISTEM PENCERNAAN MANUSIA DI SD NEGERI 72 PALEMBANG - Ristia, Deny; Idris, Muhamad; Budi Irawan, David (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Understanding concepts is the basis for meaningful understanding. Many students have difficulty understanding the material concepts of the human digestive system. Augmented Reality media offers a way to deliver material in a real and interactive way. This study aims to explore the influence of the use of Augmented Reality media on students' understanding of the human digestive system concept at SD Negeri 72 Palembang. This study uses an experimental method with a posttest only control group design. The research sample consisted of 57 students, 29 in the experimental class and 28 in the control class. The instrument used in this study is a test to measure students' understanding of concepts. The findings indicates that the average score for the experimental class was 82.03, while that for the control class was 69.54. The results of the analysis of the prerequisite test showed that the data were normally distributed (significance value of 0.200 in the experimental class and 0.163 in the control class) and homogeneous (significance value of 0.087). The results of the hypothesis test using the t-test obtained a significance value of 0.000 < 0.05, so that H₀ was rejected and Hₐ was accepted. Based on these results, it can be concluded that the use of Augmented Reality media has a significant effect on students' understanding of the human digestive system at SD Negeri 72 Palembang.